Preparation of High-Purity Normal Hexane from Reformate Raffinate by Adsorption and Distillation Processes - Jichang Liu; Tengya Ni; Juntao Liu; Benxian Shen (Adsorption Science & Technology)
In this study, a combination process of adsorption and distillation was adopted to obtain high-purity normal hexane. In the adsorption separation process, 5A zeolite was used as the adsorbent and the Shanghai Gaoqiao Petrochemical Corporation reformate raffinate containing 24.24 wt% normal hexane was separated into adsorption raffinate oil rich in non-normal paraffins and desorption oil rich in normal paraffins. At pre-specified operation conditions, concentration of n-hexane in the desorption oil reached higher than 96%. The concentrations of 3-methyl pentane and methyl cyclopentane, which are the light- and heavy-key components in the distillation tower of normal hexane, were reduced to 0.15% and 0.07%, respectively. According to the simulation results obtained using the software Aspen Plus , when the distillation tower has 15 stages, the n-hexane concentration can reach 99.02% with a recovery rate of 72.89% at the reflux ratio of 7.5. The combination process involving both adsorption and distillation has much higher efficiency than the traditional distillation process for producing the high-purity normal hexane.